Functional skeletal muscle constructs from transdifferentiated human fibroblasts - Bin Xu (Nature Portfolio, 2020)
Abstract Transdifferentiation of human non-muscle cells directly into myogenic cells by forced expression of MyoD represents one route to obtain highly desirable human myogenic cells. However, functional properties of the tissue constructs derived from these transdifferentiated cells have been rarely studied. Here, we report that three-dimensional (3D) tissue constructs engineered with iMyoD-hTERT-NHDFs, normal human dermal fibroblasts transduced with genes encoding human telomerase reverse transcriptase and doxycycline-inducible MyoD, generate detectable contractile forces in response to electrical stimuli upon MyoD expression. Withdrawal of doxycycline in the middle of 3D culture results in 3.05 and 2.28 times increases in twitch and tetanic forces, respectively, suggesting that temporally-controlled MyoD expression benefits functional myogenic differentiation of transdifferentiated myoblast-like cells. Treatment with CHIR99021, a Wnt activator, and DAPT, a Notch inhibitor, leads to further enhanced contractile forces. The ability of these abundant and potentially patient-specific and disease-specific cells to develop into functional skeletal muscle constructs makes them highly valuable for many applications, such as disease modeling.